1999
DOI: 10.1056/nejm199902253400804
|View full text |Cite|
|
Sign up to set email alerts
|

Racial Differences in the Outcome of Left Ventricular Dysfunction

Abstract: Blacks with mild-to-moderate left ventricular systolic dysfunction appear to be at higher risk for progression of heart failure and death from any cause than similarly treated whites. These results suggest that there may be racial differences in the outcome of asymptomatic and symptomatic left ventricular systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
221
2
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(234 citation statements)
references
References 17 publications
5
221
2
6
Order By: Relevance
“…Previous studies in Western CHF populations have shown a racial disparity in clinical outcome, with Blacks having a worse survival compared to Caucasians [2]. There is a paucity of data in the literature regarding the influence of race on clinical outcome in an Asian CHF population.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies in Western CHF populations have shown a racial disparity in clinical outcome, with Blacks having a worse survival compared to Caucasians [2]. There is a paucity of data in the literature regarding the influence of race on clinical outcome in an Asian CHF population.…”
Section: Introductionmentioning
confidence: 98%
“…7,20,21 The Studies of Left Ventricular Dysfunction were among the first to suggest differential HF outcomes as a function of race. 22 A post hoc analysis of the primary trial results demonstrated that mortality from HF was higher in African Americans than in Caucasians, with a 1.8-fold increase for African American men and a striking 2.4-fold increase for African American women. Subsequent studies have shown that African Americans have a more rapid progression of HF than Caucasians, 5 are more likely to have NYHA functional class III symptoms, 5 and have higher rates of HF hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the higher risk of progression of heart failure and death from any cause among blacks enrolled in the SOLVD trials are unlikely to be related to access issues; the SOLVD data suggest that differences in the natural history of ischemic and nonischemic LV dysfunction account for differences in clinical course between black and white patients. 2 …”
Section: Discussionmentioning
confidence: 99%
“…1 In an analysis of data from the studies of left ventricular dysfunction (LVD) prevention and treatment trials, blacks with mild to moderate LV systolic dysfunction were at higher risk for progression of heart failure and death from any cause than similarly treated whites. 2 National statistics show that the rate of death from heart failure in 1990 was about four times higher in black than in white subjects. 3 In this study, we attempted to evaluate the impact of patients' race on the utilization of effective medical therapy for heart failure.…”
Section: Introductionmentioning
confidence: 99%